The Influence Of Digital Marketing On Consumer Purchasing Decisions On Precast Concrete Products At Pt. Super Beton Prima - Januarsih, Ayu; Handayani, Sri; Hidayah, Nenden Restu (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the influence of social media on consumer purchasing decisions on precast concrete products at PT. Super Beton Prima to determine the effect of search engine optimization on consumer purchasing decisions on precast concrete products at PT. Super Beton Prima. The results showed that the regression equation obtained from the type of research used in this study is a quantitative method. The results showed that the regression equation obtained from the research results is as follows: From the calculation with SPSS, the regression equation is obtained: Y = 7.205 + 0.914X1 + 0.630 X2 + 0.563 X3 + 0.528 X4. There is an influence of social media (X1) on purchasing decisions (Y) at PT Super Beton Prima with a significance value of 0.000 <0.05 and t count>t table (5.320> 1.665) thus Ho is rejected and Ha is accepted. There is an influence of Search Engine Optimization (X2) on purchasing decisions (Y) at PT. Super Beton Prima with a significance value of 0.001 < 0.05 and t count> t table (8,780>1,665) thus Ho is accepted and Ha is rejected. There is an influence of marketing content (X3) on purchasing decisions (Y) at PT Super Beton Prima with a significance value of 0.000<0.05 and tcount>ttable (7,714> 1,665). Thus Ho is rejected and ha is accepted. There is an effect of paid advertising (X4) on the purchasing decision (Y) of on PT. Super Beton Prima with a significance value of 0.001 <0.05 and t count> t table (5.571>1.665). Thus Ho is rejected and ha is accepted. The value of Fsig is 0.000<0.05 and and F count>F tabel (351,219>2.72), so it can be concluded that together social media, search engine optimization, content marketing and paid advertising have an effect on purchasing decisions at PT. Super Beton Prima.